PURIFYING THOUGHT, WORD, AND DEED: APPLYING TRI KAYA PARISUDHA TO ECOLOGICAL ETHICS IN POST-FLOOD BALI - I Nyoman Alit Supandi (INTERNATIONAL JOURNAL ON HINDU CULTURE, 2025)
Recent floods across several regions of Bali—such as Denpasar, Gianyar, and Tabanan—have revealed deep ecological imbalance caused by unrestrained urbanization, deforestation, and waste mismanagement. Beyond their material destruction, these disasters signify a rupture between bhuana alit (the microcosm of human life) and bhuana agung (the macrocosm of the cosmos). This paper explores how the Hindu ethical doctrine of Tri Kaya Parisudha—the purity of thought (manacika), speech (wacika), and action (kayika)—can serve as a framework for ecological ethics and moral restoration in post-flood Bali. Using qualitative interpretive methods grounded in textual analysis and cultural observation, the study argues that reactivating Tri Kaya Parisudha fosters ecological awareness, collective responsibility, and spiritual resilience. The moral purification of individuals is inseparable from the healing of nature; hence, the path to environmental harmony must begin with ethical transformation rooted in dharma.